Geology and depositional environment of sambipitu formation in Pengkok area, Gunung Kidul, Yogyakarta, Indonesia - Siti Balqis Mohd Raflis (2020)
Yogyakarta situated in Central Java and located only 30km from the Merapi volcano area. The study area was located at Pengkok area, Gunung Kidul, Yogaykarta, Indonesia with coordinate between longitude 110°28'14.90"E to 110°30'58.05"E and 7°52'0.42"S to 7°54'43.28"S latitude. The geology, lithology unit, sedimentary facies need to update for details information in Pengkok area specially in determined their depositional environment. The objective of the study were to update a geological map with the scale of 1:25,000, to analyse the sedimentary facies in study area and to determine the depositional environemt of Sambipitu Formation. The methodes that be used in this study were lithostratigraphic column and foraminifera analysis. At the upper part of the study covered with pyroclastic breccia, epiclastic breccia, lava, epiclastic breccia sandstone, sandstone and mudstone, mudstone, carbonaceous sandstone. The tuffaceous limestone, wackestone, packstone, grainstone, rudstone and oncolites can be found at lower part study area. Previous stratigraphic measurement data and analysis show the Sambipitu Formation was fluctuation of seawater level. There were three facies analysis which were lower, middle and upper of Sambipitu Formation. The depositional enviornment of Sambipitu Formation in study area was outer neritic to upper bathyal.